Islamic finance: legal frameworks, practices and shariah criteria review - Mohamed Naim, Asmadi; Isa, Mohamad Yazid; Hamid, Mohd Liki (UUM Press, 2020)
The book provides comprehensive compilation on Islamic legal documents related to Islamic financial system consists of legal statutes, frameworks, guidelines, circulars and internal compliant manual covering Islamic banking, takaful and Islamic capital markets. Brief description of those documents are laid down to assist non-legal background readers in having comprehensive view of Islamic finance legal system.Few special focuses are done to Shariah screening methodologies for stocks, Islamic fund and real estate with special review on few sukuk issuances as to familiarize reader with the principle terms and conditions (PTC) of the sukuk. Islamic finance is not just a system but it is a way to achieve the spirit of Shariah i.e. maqasid Shariah in providing prosperity to the society in blessing ways avoiding all prohibited elements as stated in Islamic law.